Health promotion in "neverland": an interdisciplinary experience - Camila Irigonhé Ramos; Chandra da Silveira Langoni; Fernanda Brenner Morés; Júlia Schneider Hermel; Luciana Balestrin Redivo Drehmer; Marcele Peretto; Tatiana Stürmer Badalotti (Universidade de Fortaleza, 2014)
Objective: To support the personal and interpersonal upbringing of pre-school children through children's care and an expanded view of health. Data Synthesis: The Family Health Strategy, a current healthcare model in Brazil, deepens the territorialization and prioritizes actions - that must go beyond the health service - to promote health by making use of existing community locales like the school for example. In this context, the team of the Multiprofessional Residency Program in Community and Family Health has developed, between 2009 and 2010, a health education project in a Primary School that is run by the city of Porto Alegre (RS). It is a qualitative experience report on health promotion activities conducted with 48 children from four to six years old. Conclusion: It was possible to infer by the end of the activity that the children developed the possibility to establish health care relations that could be analyzed by means of their own behavior. The link established between the students and the residents and the use of playful techniques were the tools to facilitate the work. Through this work, it is possible to think about the expanded view of health based on a proposal of health promotion at schools by means of an interdisciplinary and intersectoral action. doi:10.5020/18061230.2013.p436